Teachers’ Perceptions of the Role of Elementary Schools as Agents of Student Socialization - Faslia; Muhamad Nur Intan Ode; Fitriani B (Jurnal Wawasan Sarjana, 2025)
Elementary schools are considered crucial spaces for students’ socialization, as they provide opportunities for children to develop social skills alongside academic knowledge. This study aims to examine teachers’ perceptions of the role of elementary schools in fostering social values and to explore the factors influencing the effectiveness of socialization in the classroom. A qualitative research design with a phenomenological approach was employed. Data were collected through semi-structured interviews with five elementary school teachers, focusing on their experiences in integrating social values into daily learning activities and the challenges they faced. The results indicate that teachers perceive schools as not only academic institutions but also as environments where students learn cooperation, empathy, discipline, and respect for others. Socialization occurs through classroom activities, group work, peer interactions, and teachers’ modeling of appropriate behavior. However, the study also found that the integration of social values is often limited due to the dominance of cognitive-focused curriculum objectives. In addition, school policy and culture were identified as significant factors in supporting effective socialization, with schools emphasizing character education providing greater opportunities for teachers to foster social skills consistently. The findings suggest that a balanced approach between academic and social development, supported by conducive school policies, is essential for optimizing student socialization in elementary education.